Composite catalyst and preparation method thereof, water electrolysis cathode catalyst, water electrolysis device and method for producing hydrogen by electrolyzing water
By using a composite catalyst of α-Ni(OH)2 nanosheets and PtNi alloy particles in an AEM electrolytic cell, the problem of insufficient activity of the catalyst under alkaline conditions in the prior art is solved, and a high-efficiency and low-cost hydrogen precipitation effect is achieved.
Patent Information
- Application Number
- CN202311394897.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art lacks efficient, low-cost and stable hydrogen evolution catalysts suitable for the operation characteristics of AEM electrolytic cells, especially the Pt-based catalyst has a low HER activity under alkaline conditions.
A composite catalyst was designed, including α-Ni(OH)2 nanosheets and PtNi alloy particles, prepared by a one-step solvothermal method, reducing the Pt load and optimizing the H adsorption and desorption process.
The platinum content in the catalyst is significantly reduced, the mass-specific activity of the catalyst is improved, and the hydrogen evolution overpotential is reduced, while simplifying the preparation process.
Smart Images

Figure CN119877009A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of hydrogen energy and electrocatalysis technology, and in particular, to a composite catalyst for water electrolysis and a preparation method thereof, a water electrolysis cathode catalyst, a water electrolysis device, and a method for producing hydrogen by electrolyzing water. Background Art
[0002] Hydrogen energy has attracted widespread attention due to its high energy density, cleanliness and sustainable utilization. Among various technologies for producing green hydrogen by water electrolysis, hydrogen production by water electrolysis using anion exchange membrane (AEM) can combine the low cost of alkaline water electrolysis (ALK) with the simplicity and high efficiency of water electrolysis using proton exchange membrane (PEM), and is considered to be the most promising technology for large-scale hydrogen production in the future. At present, catalysts for AEM electrolyzers are mainly based on traditional ALK electrode catalysts or PEM precious metals, and there is a lack of high-efficiency, low-cost and stable catalysts that are adapted to the operating characteristics of AEM electrolyzers. Due to its excessively high overpotential and large Tafel slope, the HER catalytic activity of traditional nickel metal under alkaline conditions is still lower than that of precious metal Pt-based catalysts. Therefore, it is necessary to develop efficient, stable, and low-Pt-loaded AEM hydrogen evolution catalysts.
[0003] Pt has a strong H adsorption capacity and has a high HER activity under acidic conditions, but Pt has a weak ability to dissociate H-OH bonds, and its HER activity under alkaline conditions is two orders of magnitude lower than that under acidic conditions. Therefore, the introduction of non-precious metals with strong H-OH dissociation ability is an effective strategy to reduce the Pt loading and improve the HER activity of Pt in alkaline media. In addition, since Pt has a strong H adsorption capacity, it is difficult for H2 to desorb from its surface, and the hydrogen evolution step can be further optimized by introducing other metals.
[0004] The patents (CN202211110543.X, 202011532266.2) reported Pt-loaded Ni(OH)2 composite materials, which were synthesized using a multi-step reaction route, i.e., Ni(OH)2 was first prepared and then Pt particles were loaded on Ni(OH)2. The preparation process is relatively complicated, and the hydrogen evolution activity and stability in alkaline media need to be improved. Summary of the invention
[0005] The purpose of the present disclosure is to provide a composite catalyst for water electrolysis and a preparation method thereof, a water electrolysis cathode catalyst, a water electrolysis device and a method for producing hydrogen by electrolyzing water, which can significantly reduce the platinum content in the catalyst, improve the mass specific activity of the catalyst, and simultaneously reduce the hydrogen evolution overpotential of the catalyst; and can also simplify the preparation process.
[0006] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a composite catalyst for electrolysis of water, wherein the XRD spectrum of the composite catalyst contains a diffraction peak of a face-centered cubic PtNi alloy and a diffraction peak of α-phase Ni(OH)2.
[0007] Optionally, the composite catalyst comprises α-Ni(OH)2 nanosheets and PtNi alloy particles; the thickness of the α-Ni(OH)2 nanosheets is 1 to 2 nm; the PtNi alloy particles are distributed on the surface of the α-Ni(OH)2 nanosheets;
[0008] The particle size of the PtNi alloy particles is 20 to 100 nm, preferably 30 to 50 nm; the PtNi alloy particles include a PtNi alloy with a face-centered cubic phase structure.
[0009] Optionally, based on the total weight of the composite catalyst, the content of the hydroxide is 30-80% by weight, and the content of the alloy particles is 20-70% by weight; preferably, the content of the hydroxide is 40-60% by weight, and the content of the alloy particles is 40-60% by weight;
[0010] Optionally, in the composite catalyst, the molar ratio of Pt element to Ni element is 0.067-0.2:1, preferably 0.1-0.15:1.
[0011] Optionally, the metal Ni in the composite catalyst comprises +0-valent Ni and +2-valent Ni; the XPSNi 2P 3 / 2 The spectrum has characteristic peaks at 853.0-853.1 eV;
[0012] Preferably, the composite catalyst has the following XPS Ni 2P 3 / 2 Spectral features:
[0013] The XPS Ni 2P 3 / 2 The peak area of the spectrum peak within the range of 850.0 to 858.5 eV in the spectrum is recorded as I1, and the XPS Ni 2P 3 / 2 The peak area of the peak in the range of 858.5 to 867.0 eV in the spectrum is recorded as I2, and X1 defined by the following formula (1) is any value in the range of 0.5 to 1.5:
[0014] X1=I1 / I2 Formula (1);
[0015] Preferably, X1 is any value in the range of 0.8 to 1.3.
[0016] A second aspect of the present disclosure provides a method for preparing a composite catalyst for water electrolysis, comprising the following steps:
[0017] S1, mixing a nickel source, a platinum source, a reducing agent and a surfactant to obtain a first material, wherein the reducing agent is selected from one or more alcohol compounds;
[0018] S2, mixing the first material with an alkali source for a second time to obtain a second material;
[0019] S3, subjecting the second material to a one-step hot solvent reaction.
[0020] Optionally, in step S1, the nickel source is selected from one or more of nickel acetylacetonate, nickel acetate, nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate and nickel aminosulfate; preferably, one or more of nickel acetylacetonate, nickel acetate and nickel chloride;
[0021] The platinum source is selected from one or more of platinum acetylacetonate, platinum chloride, chloroplatinic acid, platinum acetate, potassium chloroplatinate and ammonium chloroplatinate; preferably platinum acetylacetonate and / or chloroplatinic acid;
[0022] The alcohol compound is selected from one or more of benzyl alcohol, methanol, ethylene glycol, ethanol, isopropanol and propylene glycol;
[0023] The surfactant is selected from one or more of polyvinyl pyrrolidone, cetyl trimethyl ammonium chloride, cetyl trimethyl ammonium bromide, polyethylene glycol and sodium polyacrylate.
[0024] Optionally, in step S1, in the first material, relative to 1L of the alcohol compound, the amount of the platinum source is 0.005-0.05 mol, preferably 0.008-0.02 mol; relative to 1L of the alcohol compound, the amount of the nickel source is 0.1-0.2 mol, preferably 0.15-0.2 mol;
[0025] Preferably, the molar ratio of nickel source: platinum source is 5 to 20:1, preferably 6.67 to 10:1;
[0026] Optionally, relative to 1L of the alcohol compound, the amount of the surfactant is 5 to 30 g, preferably 10 to 20 g; preferably, the weight of the surfactant: the total weight of the nickel source and the platinum source is 1:2 to 5, preferably 1:3 to 4;
[0027] The first mixing time is 0.5 to 2 hours, and the first mixing temperature is 20 to 50° C.; preferably, the first mixing time is 0.5 to 1 hour, and the first mixing temperature is 20 to 30° C.
[0028] Optionally, in step S2, the alkali source is selected from one or both of sodium hydroxide and potassium hydroxide; optionally, the concentration of the alkali source is 1-2 mol / L, preferably 1.5-2 mol / L; the amount of the alkali source is 5-20 ml, preferably 10-20 ml; preferably, the molar ratio of alkali source: nickel source is 0.5-3:1, preferably 1-2:1;
[0029] Preferably, the second mixing time is 0.5 to 2 hours, and the second mixing temperature is 20 to 50°C; preferably, the second mixing time is 0.5 to 1 hour, and the second mixing temperature is 20 to 30°C.
[0030] Optionally, in step S3, the conditions of the one-step solvent reaction include: reaction temperature of 120-150° C., reaction time of 3-9 h, and reaction pressure of 0.2-2 MPa; preferably, reaction temperature of 120-130° C., reaction time of 3-6 h, and reaction pressure of 0.3-1.5 MPa;
[0031] Optionally, the one-step solvent reaction is carried out in a polytetrafluoroethylene reactor.
[0032] A third aspect of the present disclosure provides a composite catalyst for water electrolysis prepared according to the method described in the second aspect of the present disclosure.
[0033] The fourth aspect of the present disclosure provides a water electrolysis cathode catalyst, comprising the composite catalyst described in the first aspect or the third aspect of the present disclosure and a carbon carrier; based on the total weight of the water electrolysis cathode catalyst, the Pt content is 5 to 10 weight%, preferably 6 to 8 weight%.
[0034] The fifth aspect of the present disclosure provides an anion exchange membrane water electrolysis device, comprising an anion exchange membrane, a cathode catalyst layer, an anode catalyst layer, a cathode diffusion layer and an anode diffusion layer, wherein the cathode catalyst layer comprises the composite catalyst described in the first aspect or the third aspect of the present disclosure, or comprises the water electrolysis cathode catalyst described in the fourth aspect of the present disclosure.
[0035] The sixth aspect of the present disclosure provides a method for producing hydrogen by electrolyzing water, using the composite catalyst described in the first aspect or the third aspect of the present disclosure, or using the water electrolysis cathode catalyst described in the fourth aspect of the present disclosure, or using the anion exchange membrane water electrolysis device described in the fifth aspect of the present disclosure.
[0036] Through the above technical scheme, the present disclosure provides a composite catalyst for electrolysis of water and a preparation method thereof, a water electrolysis cathode catalyst, a water electrolysis device and a method for electrolyzing water to produce hydrogen, wherein the composite catalyst comprises α-Ni(OH)2 and PtNi alloy, wherein Ni(OH)2 can promote the adsorption of OH and the dissociation of H-OH bonds, and the PtNi alloy can improve the disadvantage that H2 is difficult to desorb on the surface of single substance Pt, optimize H adsorption and desorption and hydrogen precipitation; and a good interface is formed between the Ni(OH)2 nanosheets and the PtNi alloy partially covering the surface thereof, so that the H atoms formed by the dissociation of H2O on the surface of the Ni(OH)2 nanosheets can quickly diffuse to the nearby PtNi metal surface, reducing the migration process of the H atoms; the composite catalyst provided by the present disclosure reduces the Pt loading in the AEM catalyst by designing the composite structure of PtNi particles and Ni(OH)2 nanosheets, and at the same time, the catalyst has excellent alkaline HER activity, and its mass activity can reach several times that of commercial Pt / C catalysts. In addition, the method for preparing the composite catalyst provided by the present disclosure adopts a one-step solvothermal method to prepare the electrolytic water composite catalyst, and simultaneously performs the metal reduction and loading process, which greatly simplifies the preparation process. The preparation process is simple and highly repeatable, which is conducive to industrial scale-up.
[0037] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0039] Figure 1 The XRD diagram of the composite catalyst for electrolysis of water prepared in Example 4 of the present disclosure;
[0040] Figure 2 TEM image of the water electrolysis composite catalyst prepared in Example 2 of the present disclosure;
[0041] Figure 3 This is the XPS Ni 2p diagram of the water electrolysis composite catalyst prepared in Example 2 of the present disclosure;
[0042] Figure 4 XRD pattern of the catalyst prepared in Comparative Example 2 of the present disclosure;
[0043] Figure 5 This is a performance curve diagram of the water electrolysis composite catalyst prepared in Example 1 of the present disclosure used as a cathode catalyst for AEM water electrolysis and hydrogen evolution. DETAILED DESCRIPTION
[0044] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0045] In a first aspect, the present disclosure provides a composite catalyst for electrolysis of water, wherein an XRD spectrum of the composite catalyst contains a diffraction peak of a face-centered cubic PtNi alloy and a diffraction peak of α-phase Ni(OH)2.
[0046] The present disclosure provides a composite catalyst for electrolysis of water, wherein the composite catalyst comprises α-Ni(OH)2 and PtNi alloy, wherein Ni(OH)2 can promote the adsorption of OH and the dissociation of H-OH bonds, and the PtNi alloy improves the disadvantage that H2 is difficult to desorb on the surface of single substance Pt, and optimizes H adsorption and desorption and hydrogen precipitation; and a good interface is formed between Ni(OH)2 nanosheets and the PtNi alloy partially covering the surface thereof, so that H atoms formed by the dissociation of H2O on the surface of Ni(OH)2 nanosheets can quickly diffuse to the nearby PtNi metal surface, thereby reducing the migration process of H atoms; the composite catalyst provided by the present disclosure reduces the Pt loading in the AEM catalyst by designing the composite structure of PtNi particles and Ni(OH)2 nanosheets, and the catalyst has excellent alkaline HER activity, and its mass activity can reach several times that of commercial Pt / C catalysts.
[0047] In the present disclosure, the composite catalyst is determined to be a composite composition of α-Ni(OH)2 and PtNi alloy through XRD characterization.
[0048] The composite catalyst provided by the present disclosure includes a hydroxide and alloy particles covering at least a portion of the hydroxide; the hydroxide includes a hydroxide and alloy particles covering at least a portion of the hydroxide; the hydroxide includes α-Ni(OH)2, and the alloy particles include PtNi particles.
[0049] In one embodiment, the composite catalyst comprises α-Ni(OH)2 nanosheets and PtNi alloy particles; the thickness of the α-Ni(OH)2 nanosheets is 1 to 2 nm; the PtNi alloy particles are distributed on the surface of the α-Ni(OH)2 nanosheets;
[0050] The particle size of the PtNi alloy particles is 20 to 100 nm, preferably 30 to 50 nm; the PtNi alloy particles include a PtNi alloy with a face-centered cubic phase structure. In the present disclosure, the morphology of α-Ni(OH)2 is characterized by TEM as an ultra-thin nanosheet. The two-dimensional nanosheet structure of the α-Ni(OH)2 nanosheet has a large specific surface area, which is conducive to the anchoring of PtNi particles and can provide more reactive active sites.
[0051] In one embodiment, based on the total weight of the composite catalyst, the content of the hydroxide is 30-80% by weight, and the content of the alloy particles is 20-70% by weight; preferably, the content of the hydroxide is 40-60% by weight, and the content of the alloy particles is 40-60% by weight;
[0052] Optionally, in the composite catalyst, the molar ratio of Pt element to Ni element is 0.067 to 0.2:1, preferably 0.1 to 0.15:1. The composite catalyst provided by the present disclosure can significantly reduce the amount of precious metal platinum while ensuring high catalytic activity. The catalyst provided by the present disclosure does not contain other metals other than platinum and nickel or does not contain other metals in an amount sufficient to change the performance of the catalyst.
[0053] It should be understood that a small amount or trace amount of impurities are inevitably introduced during the preparation process of the catalyst. Apart from these impurities, the catalyst is basically composed of oxygen, hydrogen, nickel and platinum.
[0054] In one embodiment, the metal Ni in the composite catalyst contains +0 and +2 valence states;
[0055] XPS Ni 2P of the composite catalyst 3 / 2 The peak position of +0 metal Ni in the spectrum is 853.0-853.1 eV. XPS characterizes the transition metal Ni of the composite catalyst as +0 and +2 valence states, among which XPS Ni 2P 3 / 2 The peak position is between 853.0 and 853.1 eV. Compared with the diffraction peak of the standard Ni element (852.3 eV), the peak position shifts to the right, indicating that part of the electrons in the composite catalyst are transferred from the Ni element to the Pt element. There is a strong interaction between Ni and Pt, which is more conducive to improving the catalyst activity.
[0056] In a preferred embodiment, the metal Ni in the composite catalyst comprises +0-valent Ni and +2-valent Ni; the XPS Ni 2P 3 / 2 The spectrum has characteristic peaks at 853.0-853.1 eV;
[0057] Preferably, the composite catalyst has the following XPS Ni 2P 3 / 2 Spectral features:
[0058] The XPS Ni 2P 3 / 2 The peak area of the spectrum peak within the range of 850.0 to 858.5 eV in the spectrum is recorded as I1, and the XPS Ni 2P 3 / 2The peak area of the peak in the range of 858.5 to 867.0 eV in the spectrum is recorded as I2, and X1 defined by the following formula (1) is any value in the range of 0.5 to 1.5:
[0059] X1=I1 / I2 Formula (1);
[0060] Preferably, X1 is any value in the range of 0.8 to 1.3. When the ratio of the peak intensities of the two valence states of the nickel element of the composite catalyst is within the range of this embodiment, the composite catalyst has a higher catalytic activity.
[0061] A second aspect of the present disclosure provides a method for preparing a composite catalyst for water electrolysis, comprising the following steps:
[0062] S1, mixing a nickel source, a platinum source, a reducing agent and a surfactant to obtain a first material, wherein the reducing agent is selected from one or more alcohol compounds;
[0063] S2, mixing the first material with an alkali source for a second time to obtain a second material;
[0064] S3, subjecting the second material to a one-step hot solvent reaction.
[0065] In the preparation method provided by the present disclosure, a nickel source, a platinum source, a reducing agent and a surfactant are first mixed, so that the platinum source and the nickel source can be fully mixed, and a platinum-nickel alloy structure is prepared after a hot solvent reaction; then the first material is mixed with an alkali source so that part of the nickel source can be precipitated to obtain flaky nickel hydroxide; finally, a solvent thermal reaction is performed to prepare a water electrolysis composite catalyst, and a metal reduction and loading process is performed at the same time, which greatly simplifies the preparation process, and the preparation process is simple and highly repeatable, which is conducive to industrial scale-up.
[0066] In one embodiment, in step S1, the nickel source is selected from one or more of nickel acetylacetonate, nickel acetate, nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate and nickel aminosulfate; preferably, one or more of nickel acetylacetonate, nickel acetate and nickel chloride;
[0067] The platinum source is selected from one or more of platinum acetylacetonate, platinum chloride, chloroplatinic acid, platinum acetate, potassium chloroplatinate and ammonium chloroplatinate; preferably one or more of platinum acetylacetonate and chloroplatinic acid;
[0068] The alcohol compound is selected from one or more of benzyl alcohol, methanol, ethylene glycol, ethanol, isopropanol and propylene glycol;
[0069] The surfactant is selected from one or more of polyvinyl pyrrolidone, cetyl trimethyl ammonium chloride, cetyl trimethyl ammonium bromide, polyethylene glycol and sodium polyacrylate.
[0070] In the present disclosure, during the first mixing of the platinum source and the nickel source, heating or not heating (preferably not heating) and stirring or not stirring (preferably stirring) may be performed.
[0071] In one embodiment, in step S1, in the first material, the concentration of the nickel source is 0.1-0.2 mol / L, preferably 0.15-0.2 mol / L; the concentration of the platinum source is 0.005-0.01 mol / L, preferably 0.008-0.01 mol / L; optionally, the molar ratio of the nickel source: platinum source is 5-20:1, preferably 6.67-10:1; the concentration of the surfactant is 5-30 g / L, preferably 10-20 g / L.
[0072] In one embodiment, the first mixing time is 0.5 to 2 hours, and the first mixing temperature is 20 to 50° C.; preferably, the first mixing time is 0.5 to 1 hour, and the first mixing temperature is 20 to 30° C. The conditions provided in this embodiment can promote sufficient mixing of the metal source, the reducing agent, and the surfactant.
[0073] In one embodiment, in step S2, the alkali source is selected from one or more of sodium hydroxide and potassium hydroxide; optionally, the concentration of the alkali source is 1-2 mol / L, preferably 1.5-2 mol / L; the amount of the alkali source is 5-20 ml, preferably 10-20 ml; preferably, the molar ratio of alkali source: nickel source is 0.5-3:1, preferably 1-2:1.
[0074] In the present disclosure, during the process of adding the alkali source in step S2, heating or not heating (preferably not heating) and stirring or not stirring (preferably stirring) may be performed.
[0075] In a specific embodiment, the second mixing time is 0.5 to 2 hours, and the second mixing temperature is 20 to 50° C.; preferably, the second mixing time is 0.5 to 1 hour, and the second mixing temperature is 20 to 30° C. The second mixing conditions provided in this embodiment can promote the full mixing of the alkali source and the aforementioned first material.
[0076] In one embodiment, in step S3, the conditions of the one-step solvent reaction include: reaction temperature of 120-150° C., reaction time of 3-9 h, and reaction pressure of 0.2-2 MPa; preferably, the reaction temperature is 120-130° C., reaction time of 3-6 h, and reaction pressure of 0.3-1.5 MPa.
[0077] In a specific embodiment, the one-step solvent reaction is carried out in a polytetrafluoroethylene reactor.
[0078] In a specific embodiment, the method further comprises step S4: washing the solid precipitate obtained in step S3 until it becomes neutral, and then performing solid-liquid separation, drying and grinding. The reagent used for the washing process may be one or more of ethanol, water and cyclohexane.
[0079] In the present disclosure, all solid-liquid separation methods can be conventional separation methods in the art, as long as the purpose of solid-liquid separation can be achieved. For example, vacuum filtration, centrifugal separation, etc. When the solid-liquid separation method is centrifugal separation, the speed of centrifugal separation is 11000-14000rpm, and the time is 10-20min. According to the catalyst preparation method disclosed in the present disclosure, in step S4, the method for solid-liquid separation is preferably centrifugal separation. In the present disclosure, all washing methods including the aforementioned are conventional methods in the art, as long as the purpose of washing the solid clean can be achieved, for example, ultrasonic washing can be used.
[0080] According to the catalyst preparation method disclosed in the present invention, step S4 further includes: drying the solid product obtained after solid-liquid separation, and the drying method can be any conventional method in the art, for example, an oven or a vacuum freeze oven can be used for drying. The drying conditions include: a temperature of 30 to 60°C, preferably 30 to 50°C; a time of 6 to 24 hours, preferably 12 to 24 hours.
[0081] A third aspect of the present disclosure provides a composite catalyst for water electrolysis prepared according to the method described in the second aspect of the present disclosure.
[0082] A fourth aspect of the present disclosure provides a water electrolysis cathode catalyst, comprising the composite catalyst described in the first aspect or the third aspect of the present disclosure.
[0083] In a specific embodiment, the water electrolysis cathode catalyst comprises the composite catalyst described in the first aspect or the third aspect of the present disclosure and a carbon support, and the composite catalyst is supported on the carbon support. The catalyst is recorded as PtNi-Ni(OH)2 / C, and the content of Pt is 5 to 10% by weight, preferably 6 to 8% by weight, based on the total weight of the PtNi-Ni(OH)2 / C.
[0084] In a specific embodiment, the water electrolysis cathode catalyst is prepared by a preparation method comprising the following steps: dispersing a PtNi-Ni(OH)2 composite catalyst and conductive carbon black in a cyclohexane solution, stirring overnight, washing once with ethanol after centrifugation, and drying to obtain a PtNi-Ni(OH)2 / C catalyst. The weight ratio of the catalyst to the conductive carbon black is 0.2 to 1.5:1, preferably 0.5 to 0.8:1.
[0085] The fifth aspect of the present disclosure provides an anion exchange membrane water electrolysis device, comprising an anion exchange membrane, a cathode catalyst layer, an anode catalyst layer, a cathode diffusion layer and an anode diffusion layer, wherein the cathode catalyst layer comprises the composite catalyst described in the first aspect or the third aspect of the present disclosure, or comprises the water electrolysis cathode catalyst described in the fourth aspect of the present disclosure.
[0086] The sixth aspect of the present disclosure provides a method for producing hydrogen by electrolyzing water, using the composite catalyst described in the first aspect or the third aspect of the present disclosure, or using the water electrolysis cathode catalyst described in the fourth aspect of the present disclosure, or using the anion exchange membrane water electrolysis device described in the fifth aspect of the present disclosure.
[0087] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can all be obtained through commercial sources.
[0088] Instruments, methods and conditions for XPS analysis: The present disclosure uses an X-ray photoelectron spectroscopy (XPS) to detect the elements on the surface of the material. The X-ray photoelectron spectroscopy used is an ESCALab220i-XL X-ray electron spectrometer equipped with Avantage V5.926 software produced by VG Scientific. The X-ray photoelectron spectroscopy analysis test conditions are as follows: the excitation source is monochromatic A1Kα X-ray, the power is 330W, and the basic vacuum during the analysis test is 3×10 -9 In addition, the electron binding energy was calibrated using the C1s peak (284.3 eV) of elemental carbon.
[0089] TEM analysis instrument, method and conditions: The transmission electron microscope (TEM) used in the present disclosure is a JEM-2100 (TEM) (JEOL Ltd.), and the transmission electron microscope test conditions are:
[0090] The accelerating voltage was 200 kV.
[0091] Instruments, methods and conditions for XRD analysis: X-ray diffraction analysis (XRD) was performed on a Shimadzu XRD-6000 X-ray diffractometer, Japan. The test conditions included: tube voltage 40 kV, tube current 40 mA, Cu target Kα radiation, 2θ scanning range 5° to 80°. The average primary particle size of the sample was calculated based on the Scherrer formula using the measured XRD pattern.
[0092] The testing method for the thickness of α-Ni(OH)2 nanosheets is as follows: in the TEM test image of the sample, 50 nanosheets perpendicular to the test surface are randomly selected to measure the thickness of a single layer of nanosheets.
[0093] Example 1
[0094] (1) Weigh 0.39 g (1 mmol) of acetylacetonate platinum, 2.57 g (10 mmol) of acetylacetonate nickel, and 0.8 g of polyvinyl pyrrolidone (PVP, molecular weight 8000-10000), disperse them in 50 mL of benzyl alcohol solution (analytical grade), mix them, and stir them at room temperature for 60 min to obtain a first material; wherein the concentration of the platinum source is 0.02 mol / L relative to the alcohol compound, the concentration of the nickel source is 0.2 mol / L, and the molar ratio of the nickel source to the platinum source is 10:1; relative to 1 L of the alcohol compound, the amount of the surfactant is 16 g, and the weight of the surfactant: the total weight of the nickel source and the platinum source is 1:3.7;
[0096] (2) adding 10 mL of NaOH solution (1.5 mol / L, 15 mmol) to the first material, with the molar ratio of alkali source to nickel source being 1.5:1, and stirring at room temperature for 30 min to obtain a second material;
[0097] (3) The second material was transferred to a polytetrafluoroethylene reactor and placed in a 120° C. oven for reaction for 6 h at a reaction pressure of 0.6 MPa;
[0098] (4) After cooling, the solid precipitate was obtained by centrifugation, and then ultrasonic centrifugation was continued with ethanol at a speed of 13000 rpm for 10 min until the pH of the upper layer solution was neutral, and the washing process was completed;
[0099] (5) The washed solid was placed in a vacuum drying oven, dried overnight, and ground to obtain a PtNi-Ni(OH)2 composite catalyst A1.
[0100] The alkaline HER (electrochemical hydrogen evolution reaction) test results of composite catalyst A1 are as follows: Figure 5 As shown by Figure 5 It can be seen that the catalyst has a current density of 10 mA / cm 2 The overpotential for hydrogen evolution is 68.2 mV; at an overpotential of 50 mV, the mass activity is 1.54 mA / μg Pt .
[0101] Example 2
[0102] In this example, catalyst A2 is prepared by referring to the preparation method of Example 1. The difference from Example 1 is that the reaction temperature in the one-step hot solvent reaction is 130° C. and the reaction time is 3 h. The rest of the process is the same as Example 1.
[0103] The TEM image of composite catalyst A2 is shown in Figure 2 As shown, TEM results show that in the water electrolysis composite catalyst synthesized by the method disclosed in the present invention, the morphology of α-Ni(OH)2 is ultra-thin nanosheets with a thickness of 1 to 2 nm, and the alloy is nanoparticles with a particle size range of 30 to 50 nm.
[0104] The XPS spectrum of composite catalyst A2 is shown in Figure 3 As shown, according to Figure 3 It can be seen that the XPS results of Ni 2p show that in the water electrolysis composite catalyst synthesized by the method provided by the present disclosure, the binding energy of 850.0-858.5 eV (representing the +0 valence state Ni2P 3 / 2 diffraction peak) and 858.5~867.0eV (representing +2 valence state Ni 2P 3 / 2 diffraction peak) respectively have spectral peaks, indicating that the nickel in the composite catalyst is in +0 valence state and +2 valence state, and the content ratio of +0 valence state to +2 valence state (i.e., the value of X1) is 1.2:1. Further, according to Figure 3 and standard +0 valence Ni 2P 3 / 2 From the comparison of the diffraction peaks (852.3 eV), it can be seen that in the water electrolysis composite catalyst synthesized by the method disclosed in the present invention, the diffraction peak of Ni shifts to the right, indicating that part of the electrons are transferred from the Ni element to the Pt element, and there is a strong interaction between Ni and Pt, which is more conducive to improving the activity.
[0105] Example 3
[0106] In this example, catalyst A3 was prepared by referring to the preparation method of Example 1. The difference from Example 1 is that 3 mL of NaOH solution (0.5 mol / L, 1.5 mmol) was added, and the molar ratio of the alkali source to the nickel source was 0.15:1. The rest of the process was the same as that of Example 1 to prepare a composite catalyst.
[0107] Example 4
[0108] In this example, catalyst A4 was prepared by referring to the preparation method of Example 1, which is different from Example 1 in that: 0.19 g (0.5 mmol) of acetylacetonate platinum and 2.57 g (10 mmol) of acetylacetonate nickel were weighed, the concentration of the platinum source was 0.01 mol / L, the concentration of the nickel source was 0.2 mol / L, and the molar ratio of the nickel source to the platinum source was 20:1 relative to the alcohol compound; the weight of the surfactant: the total weight of the nickel source and the platinum source was 1:3.45; the rest of the process was the same as in Example 1 to prepare a composite catalyst.
[0109] The XRD spectrum of composite catalyst A4 is shown in Figure 1 As shown, the XRD results show that the composition of the water electrolysis composite catalyst synthesized by the method disclosed in the present invention is α-phase Ni(OH)2 and face-centered cubic phase PtNi alloy.
[0110] Example 5
[0111] In this example, catalyst A5 is prepared by referring to the preparation method of Example 1, and the difference from Example 1 is that: 0.39 g (1 mmol) of acetylacetonate platinum and 1.29 g (5 mmol) of acetylacetonate nickel are weighed, and the molar ratio of nickel source: platinum source is 5:1; the weight of surfactant: the total weight of nickel source and platinum source is 1:2.1, and the molar ratio of alkali source: nickel source is 3:1; the rest of the process is the same as Example 1.
[0112] Example 6
[0113] In this example, catalyst A6 is prepared by referring to the preparation method of Example 1. The difference from Example 1 is that the platinum source is replaced by chloroplatinic acid, the nickel source is replaced by nickel acetate, the reducing agent is replaced by ethylene glycol; the surfactant is replaced by hexadecyltrimethylammonium chloride, and the rest of the process is the same as Example 1.
[0114] Example 7
[0115] This example prepares catalyst A7 by referring to the preparation method of Example 1, and the difference from Example 1 is that:
[0116] Weigh 0.16g (0.4mmol) of platinum acetylacetonate, 1.29g (5mmol) of nickel acetylacetonate, and 0.4g of polyvinyl pyrrolidone (PVP, molecular weight 8000-10000) and disperse them in 50mL of benzyl alcohol solution (analytical grade), stir at room temperature for 60min, and obtain the first material; wherein the concentration of the platinum source is 0.008mol / L, the concentration of the nickel source is 0.1mol / L, and the molar ratio of the nickel source to the platinum source is 12.5:1 relative to 1L of the alcohol compound; the amount of the surfactant is 8g, and the weight of the surfactant: the total weight of the nickel source and the platinum source is 1:3.62. The rest of the process is the same as in Example 1, and a composite catalyst is prepared.
[0117] Example 8
[0118] This example prepares catalyst A8 by referring to the preparation method of Example 1, and the difference from Example 1 is that:
[0119] 5 mL of NaOH solution (1 mol / L, 5 mmol) was added to the first material, the molar ratio of alkali source: nickel source was 0.5:1, and the mixture was stirred at room temperature for 30 min to obtain the second material; the rest of the process was the same as in Example 1 to prepare a composite catalyst.
[0120] Example 9
[0121] This example prepares catalyst A9 by referring to the preparation method of Example 1, and the difference from Example 1 is that:
[0122] (1) Weighing platinum acetylacetonate, nickel acetylacetonate, and polyvinyl pyrrolidone, dispersing them in a benzyl alcohol solution (analytical grade), mixing them, and stirring them at 50° C. for 120 min to obtain a first material;
[0123] (2) adding NaOH solution to the first material and stirring at 50° C. for 120 min to obtain a second material;
[0124] (3) The second material was transferred to a polytetrafluoroethylene reactor and placed in a 150° C. oven for reaction for 3 h at a reaction pressure of 2 MPa;
[0125] The remaining process is the same as in Example 1 to prepare a composite catalyst.
[0126] Example 10
[0127] This example prepares catalyst A10 by referring to the preparation method of Example 1, and the difference from Example 1 is that:
[0128] (1) Weighing platinum acetylacetonate, nickel acetylacetonate, and polyvinyl pyrrolidone, dispersing them in a benzyl alcohol solution (analytical grade), mixing them, and stirring them at 80° C. for 180 min to obtain a first material;
[0129] (2) adding NaOH solution to the first material and stirring at 80° C. for 180 min to obtain a second material;
[0130] (3) The second material was transferred to a polytetrafluoroethylene reactor and placed in an oven at 180° C. for reaction for 12 h at a reaction pressure of 2 MPa;
[0131] The remaining process is the same as in Example 1 to prepare a composite catalyst.
[0132] Comparative Example 1
[0133] Catalyst D1 was prepared by referring to the method of Example 1. The difference from Example 1 is that the reaction temperature in the one-step hot solvent reaction is 120° C. and the reaction time is 1 h. The rest of the process is the same as Example 1.
[0134] Comparative Example 2
[0135] In this comparative example, catalyst D2 was prepared by referring to the method of Example 1, which differs from Example 1 in that 0.18 g (0.46 mmol) of platinum acetylacetonate and 0.355 g (1.38 mmol) of nickel acetylacetonate were weighed, and no NaOH solution was added. The rest of the process was the same as Example 1.
[0136] The XRD pattern of catalyst D2 is as follows: Figure 4 As shown, the XRD results show that the catalyst synthesized by the method of Comparative Example 2 is a PtNi alloy catalyst. Figure 1 and Figure 4By comparison, Figure 4 There are no diffraction peaks of α-phase Ni(OH)2 in the XRD spectrum (2θ is 18.7°, 33.1°, 38.5°, 59.1°, 62.7°, 69.3° and 72.7°).
[0137] Comparative Example 3
[0138] 0.465 g (5 mmol) of commercial nickel hydroxide and 0.13 g of commercial platinum-carbon catalyst were weighed and dispersed in an ethanol solution. After stirring at room temperature for 12 h, the solid precipitate was obtained by centrifugation. The solid precipitate was placed in a vacuum drying oven, dried overnight, and ground to obtain catalyst D3.
[0139] Comparative Example 4
[0140] A commercial platinum-carbon catalyst was used, represented by the number D4, produced by Johnson Matthey, wherein the mass fraction of platinum was 40 weight %.
[0141] The component contents, structural parameters and X1 values of the catalysts prepared in the above examples and comparative examples are listed in the following Table 1.
[0142] Table 1
[0143]
[0144]
[0145] In Table 1, X1=0 means that there is no zero-valent Ni in the catalyst and that the catalyst contains 100% +2-valent Ni. The symbol " / " means that there is no Ni.
[0146] Test Case
[0147] This test example is used to illustrate the effect of the catalysts prepared in the above examples and comparative examples in HER performance tests.
[0148] The catalyst prepared in the above examples and comparative examples was loaded on a carbon black carrier to prepare a water electrolysis cathode catalyst: 0.4 g of the composite catalyst and 0.6 g of conductive carbon black were dispersed in 100 mL of cyclohexane solution, stirred overnight (12 h), washed once with ethanol after centrifugation, and dried to obtain a PtNi-Ni(OH)2 / C catalyst. The mass ratio of the catalyst to the conductive carbon black was 40 wt %:60 wt %.
[0149] Method for electrochemical hydrogen evolution reaction: The electrochemical workstation model is PARSTAT3000A-DX, and the rotating disk electrode model is 636A. A three-electrode system is adopted, the reference electrode is a mercury oxide electrode, the counter electrode is a graphite rod, and the working electrode is a glassy carbon electrode. The electrolyte used under alkaline conditions is a 1M KOH solution. 2mg of PtNi-Ni(OH)2 / C catalyst is uniformly dispersed in a mixed solution of 0.7mL isopropanol, 0.3mL water and 10uL 5wt% Nafion solution (perfluorosulfonic acid type polymer solution) by ultrasonic means (the mass ratio of catalyst to Nafion is 10:1), 5μL is coated on the surface of the glassy carbon electrode, and the working electrode is obtained after natural drying. The electrode of commercial Pt / C catalyst was prepared by uniformly dispersing 1 mg of Pt / C catalyst in a mixed solution of 0.7 mL of isopropanol, 0.3 mL of water and 10 μL of 5 wt% Nafion solution (perfluorosulfonic acid polymer solution) by ultrasonic method (the mass ratio of catalyst to Nafion was 10:1), taking 5 μL to coat the surface of glassy carbon electrode, and drying naturally to obtain the working electrode. Before the test, hydrogen was passed for 30 minutes to saturate the solution with oxygen, and the scanning range of the linear polarization curve was -0.2 to 0.2 V (vs RHE), and the scanning rate was 5 mV / s.
[0150] Calculation method of mass activity: At an overpotential of 50 mV, the corresponding current is divided by the mass of platinum on the glassy carbon electrode to obtain the mass specific activity.
[0151] Instrument, method and conditions for testing the content of platinum: The present disclosure uses inductively coupled plasma mass spectrometry (ICP-MS) to test the content of Pt ions in the reaction solution after preparing PtNi-Ni(OH)2 (i.e., the liquid after centrifugation in step (4)), and obtains the content of platinum in the catalyst through conversion. The model of ICP-MS is VISTA-710ES (Varian, USA).
[0152] The test results are listed in Table 2 below.
[0153] Table 2
[0154]
[0155] According to the data in Table 2, the electrolytic water composite catalyst prepared by the method of the present disclosure has the advantage of significantly higher mass activity than commercial platinum carbon while reducing the amount of precious metal platinum, and has significantly better electrocatalytic performance when used as a cathode catalyst for anion exchange membrane water electrolysis hydrogen production. In addition, in the method provided by the present disclosure, the activity of the catalyst can be further optimized by the platinum-nickel ratio, reaction time, NaOH dosage, etc.
[0156] According to the comparison between Example 1 and Comparative Example 1, when the reaction time in Comparative Example 1 is too short, Pt is almost not reduced, the catalyst contains only a large amount of Ni element, and the hydrogen evolution activity of the catalyst decreases significantly. Therefore, the one-step hot solvent reaction conditions (such as reaction time) provided in the present disclosure can further improve the activity of the catalyst.
[0157] According to the comparison between Example 1 and Comparative Example 2, when NaOH solution is not added during the reaction, the composition of the catalyst is only PtNi alloy, and the hydrogen evolution activity of the catalyst decreases, which further proves that when PtNi alloy and Ni(OH)2 form a composite catalyst, the synergistic coupling effect of PtNi and Ni(OH)2 can further improve the activity of the catalyst.
[0158] According to the comparison between Example 1 and Comparative Example 3, when Ni(OH)2 is mechanically mixed with commercial Pt / C, the hydrogen evolution activity of the catalyst decreases, further proving that the good interface between Ni(OH)2 nanosheets and the PtNi alloy partially covering its surface can further improve the activity of the catalyst.
[0159] According to the comparison between Example 1 and Examples 4 to 5 and Examples 7 to 8, it can be seen that in the catalyst preparation process, Example 1 prepares the catalyst according to the preferred conditions provided in the present disclosure. Compared with the catalysts prepared in Examples 4 to 5 and Examples 7 to 8, the catalyst prepared in Example 1 has a lower hydrogen evolution overpotential and a higher mass activity.
[0160] According to the comparison between Example 3 and Example 8, the molar ratio of the alkali source to the nickel source in Example 8 is within the range provided in the present disclosure, while the molar ratio of the alkali source to the nickel source in Example 3 is not within the range provided in the present disclosure. Compared with the catalyst prepared in Example 3, the catalyst prepared in Example 8 has a lower hydrogen evolution overpotential and a higher mass activity.
[0161] According to the comparison between Example 9 and Example 10, it can be seen that Example 9 prepares the catalyst according to the range of process conditions provided in the present disclosure, and compared with the catalyst prepared in Example 10, the catalyst prepared in Example 9 has a lower hydrogen evolution overpotential and a higher mass activity; further, according to the comparison between Example 1 and Example 9, it can be seen that Example 1 prepares the catalyst according to the preferred preparation conditions provided in the present disclosure, and compared with the catalyst prepared in Example 9, the catalyst prepared in Example 1 has a lower hydrogen evolution overpotential and a higher mass activity.
[0162] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0163] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0164] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A composite catalyst for electrolysis of water, characterized in that: The XRD spectrum of the composite catalyst contains the diffraction peak of the PtNi alloy with a face-centered cubic structure and the diffraction peak of α-phase Ni(OH)2.
2. The composite catalyst according to claim 1, characterized in that The composite catalyst comprises α-Ni(OH)2 nanosheets and PtNi alloy particles; the thickness of the α-Ni(OH)2 nanosheets is 1 to 2 nm; the PtNi alloy particles are distributed on the surface of the α-Ni(OH)2 nanosheets; The particle size of the PtNi alloy particles is 20 to 100 nm, preferably 30 to 50 nm; the PtNi alloy particles include a PtNi alloy with a face-centered cubic phase structure.
3. The composite catalyst according to claim 1, characterized in that Based on the total weight of the composite catalyst, the content of Ni(OH)2 is 30 to 80% by weight, and the content of PtNi alloy particles is 20 to 70% by weight; preferably, the content of Ni(OH)2 is 40 to 60% by weight, and the content of PtNi alloy particles is 40 to 60% by weight; Optionally, in the composite catalyst, the molar ratio of Pt element to Ni element is 0.067-0.2:1, preferably 0.1-0.15:
1.
4. The composite catalyst according to claim 1, characterized in that The metal Ni in the composite catalyst comprises +0-valent Ni and +2-valent Ni; the XPS Ni 2P 3 / 2 The spectrum has characteristic peaks at 853.0-853.1 eV; Preferably, the composite catalyst has the following XPS Ni 2P 3 / 2 Spectral features: The XPS Ni 2P 3 / 2 The peak area of the spectrum peak within the range of 850.0 to 858.5 eV in the spectrum is recorded as I1, and the XPS Ni 2P 3 / 2 The peak area of the peak in the range of 858.5 to 867.0 eV in the spectrum is recorded as I2, and X1 defined by the following formula (1) is any value in the range of 0.5 to 1.5: X1=I1 / I2 Formula (1); Preferably, X1 is any value in the range of 0.8 to 1.
3.
5. A method for preparing a composite catalyst for water electrolysis, characterized in that: The following steps are involved: S1, mixing a nickel source, a platinum source, a reducing agent and a surfactant to obtain a first material, wherein the reducing agent is selected from one or more alcohol compounds; S2, mixing the first material with an alkali source for a second time to obtain a second material; S3, subjecting the second material to a one-step hot solvent reaction.
6. The method according to claim 5, characterized in that In step S1, the nickel source is selected from one or more of nickel acetylacetonate, nickel acetate, nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate and nickel aminosulfate; preferably, one or more of nickel acetylacetonate, nickel acetate and nickel chloride; The platinum source is selected from one or more of platinum acetylacetonate, platinum chloride, chloroplatinic acid, platinum acetate, potassium chloroplatinate and ammonium chloroplatinate; preferably platinum acetylacetonate and / or chloroplatinic acid; The alcohol compound is selected from one or more of benzyl alcohol, methanol, ethylene glycol, ethanol, isopropanol and propylene glycol; The surfactant is selected from one or more of polyvinyl pyrrolidone, cetyl trimethyl ammonium chloride, cetyl trimethyl ammonium bromide, polyethylene glycol and sodium polyacrylate.
7. The method according to claim 5, characterized in that In step S1, in the first material, the amount of the platinum source is 0.005-0.05 mol, preferably 0.008-0.02 mol, relative to 1 L of the alcohol compound; the amount of the nickel source is 0.1-0.2 mol, preferably 0.15-0.2 mol, relative to 1 L of the alcohol compound; Preferably, the molar ratio of nickel source: platinum source is 5 to 20:1, preferably 6.67 to 10:1; Optionally, relative to 1L of the alcohol compound, the amount of the surfactant is 5 to 30 g, preferably 10 to 20 g; preferably, the weight of the surfactant: the total weight of the nickel source and the platinum source is 1:2 to 5, preferably 1:3 to 4; The first mixing time is 0.5 to 2 hours, and the first mixing temperature is 20 to 50° C.; preferably, the first mixing time is 0.5 to 1 hour, and the first mixing temperature is 20 to 30° C.
8. The method according to claim 5, characterized in that In step S2, the alkali source is selected from one or both of sodium hydroxide and potassium hydroxide; optionally, the concentration of the alkali source is 1-2 mol / L, preferably 1.5-2 mol / L; the amount of the alkali source is 5-20 ml, preferably 10-20 ml; preferably, the molar ratio of alkali source: nickel source is 0.5-3:1, preferably 1-2:1; Preferably, the second mixing time is 0.5 to 2 hours, and the second mixing temperature is 20 to 50°C; preferably, the second mixing time is 0.5 to 1 hour, and the second mixing temperature is 20 to 30°C.
9. The method according to claim 5, characterized in that In step S3, the conditions of the one-step hot solvent reaction include: reaction temperature of 120-150° C., reaction time of 3-9 h, and reaction pressure of 0.2-2 MPa; preferably, reaction temperature of 120-130° C., reaction time of 3-6 h, and reaction pressure of 0.3-1.5 MPa; Optionally, the one-step hot solvent reaction is carried out in a polytetrafluoroethylene reactor.
10. A composite catalyst for water electrolysis prepared according to the method of any one of claims 5 to 9.
11. A cathode catalyst for water electrolysis, characterized in that: The water electrolysis cathode catalyst comprises the composite catalyst according to any one of claims 1 to 4 and 10 and a carbon carrier; based on the total weight of the water electrolysis cathode catalyst, the content of Pt is 5 to 10% by weight, preferably 6 to 8% by weight.
12. An anion exchange membrane water electrolysis device, comprising an anion exchange membrane, a cathode catalyst layer, an anode catalyst layer, a cathode diffusion layer and an anode diffusion layer, characterized in that: The cathode catalyst layer comprises the composite catalyst according to any one of claims 1 to 4 and 10, or comprises the water electrolysis cathode catalyst according to claim 11.
13. A method for producing hydrogen by electrolyzing water, characterized in that: The composite catalyst described in any one of claims 1 to 4 and 10, or the water electrolysis cathode catalyst described in claim 11, or the anion exchange membrane water electrolysis device described in claim 12 is used.
Citation Information
Patent Citations
PtNi alloy / graphene combined nanometer catalyst with hollow structure and preparation method thereof
CN102430413A
Cluster-type PtNi alloy nano catalyst and preparation method and application thereof
CN106994352A
Pt-loaded Fe-doped alpha-phase nickel hydroxide nanosheet array material, and preparation method and application thereof
CN110575836A
Membrane electrode alkaline photoelectrolysis water catalyst as well as preparation method and application thereof
CN112058275A
Method for preparing AEM water electrolysis anode catalyst material and application
CN116083947A